Blood pro-oxidant/antioxidant balance in young men with class II obesity after 20 sessions of whole body cryostimulation: a preliminary study - Wanda Pilch; Joanna Wyrostek; Anna Piotrowska; Olga Czerwińska-Ledwig; Roxana Zuziak; Ewa Sadowska-Krępa; Marcin Maciejczyk; Małgorzata Żychowska (Taylor & Francis Group, 2021)
Objectives: In obesity, there is a shift in the pro-oxidative-antioxidant balance towards the oxidationreactions. However, it has been shown that in people with normal body composition, after a series of whole-body cryotherapy (WBC), the balance shifts in the opposite direction. Design: The aim of the study was to assess the impact of 20 WBC treatments on blood pro-oxidative-antioxidant balance. Interventions: Study included 14 obese (BMI > 35) and 10 non-obese volunteers. Methods: The total antioxidative (TAS/TAC) and pro-oxidative status (TOS/TOC) in serum and activity of antioxidant enzymes in erythrocytes were determined before the first and 2 hours after the last cryostimulation. Results: In the obese group, a significantly higher level of TOS/TOC, and its significant decrease after the WBC series, was observed. Cryotherapy had no influence on TAS/TAC level which was similar in both groups. Changes in activity of antioxidant enzymes were multidirectional. An increase in CAT activity in the obese group was observed. OSI, both before and after a series of treatments, was significantly higher in obese subjects. Conclusions: A beneficial effect on the level of TOS/TOC and CAT activity was indicated, but the proposed number of treatments for patients with class II obesity turned out to be insufficient. Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12619000524190.